Revitalisasi Pembelajaran Menulis pada Generasi Digital: Kajian Pustaka tentang Strategi Pengajaran dalam Konteks Pembelajaran Abad 21 - Anita Candra Dewi; Irma Satriani (FKIP UNSULTRA, 2026)
The development of digital technology has brought significant changes to the world of education, particularly in the teaching of writing to secondary school students. The digital generation tends to be more interested in visual and interactive media than conventional texts, resulting in low interest in reading and writing. This study aims to analyze various innovative and relevant writing learning strategies to address the challenges of 21st-century learning. This study used a qualitative approach with a library research method sourced from scientific journals, academic books, and other relevant publications. The results of the study indicate that the integration of digital technology in writing learning can increase student engagement and creativity. In addition, the implementation of the Project-Based Learning model, collaborative approaches, and contextual learning have proven effective in significantly improving students' writing skills. Strengthening literacy through children's literature also contributes to developing students' imagination, vocabulary, and expressive abilities. However, various challenges remain, such as limited access to technology, differences in student abilities, and a lack of variety in learning methods. Therefore, the role of teachers is crucial in designing innovative, adaptive, and student-centered learning strategies. By integrating technology, collaboration, and real-life contexts, writing learning is expected to be more effective, meaningful, and able to continuously improve students' literacy skills.